IS OLODUMARE, GOD IN YORUBA BELIEF, GOD?: : A RESPONSE TO BENSON O. IGBOIN - Oladipupo, Sunday Layi (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2016)
Olodumare the Yoruba word for Supreme Being has attracted comments, interpretations and misinterpretations from different scholars of both Yoruba and non-Yoruba extractions. E. Bolaji Idowu, John Ayotunde Bewaji, Kazeem Ademola Fayemi, Kola Abimbola analyses manifest some seemingly contradictions upon which was hinged by Benson O. Igboin, in his paper â€œIs Olodumare, God in Yoruba Belief, God?â€ From their explanation, Igboin demand for the true nature of Olodumare having conceded that Olodumare and the Christian God are not and cannot be the same. Specifically, Igboin asked Olodumare, who are you? This paper, therefore, aims at providing an insight to the real nature of Olodumare in Yoruba worldview. It argues that God is nothing other than the English meaning or interpretation of the Supreme Being. The paper posits that Igboinâ€™s pairs of Esu and Olodumare of which one is true and faithful to Yoruba traditional Religion and the other true and faithful to Christianity in Yoruba land does not hold water. Using analytical method of philosophical inquiry, the paper concludes that Olodumare in Yoruba traditional Religion cannot be equated with the concept of God as conceived in Christianity neither could it be bifurcated. He is sufficiently a Supreme Being in Yoruba theology